Ultimate elastic wall stress (UEWS) test of glass fibre reinforced epoxy (GRE) pipe - Mohd Shukry, Abdul Majid; Assaleh, T. A.; Gibson, A. G.; Hale, J. M.; A., Fahrer; Rookus, C. A. P.; M., Hekman (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/